Implementasi Pembangunan Zona Integritas Wilayah Bebas dari Korupsi (WBK) di Kantor Bersama Samsat Surabaya Barat - Anggara, Donny; Pramono, Sapto (Soetomo Magister Ilmu Administrasi, 2025)
Implementation of public services is an effort to fulfill community needs carried out by the government. However, in its implementation, Public Service Implementation still has several shortcomings. This includes the implementation of the Integrity Zone Towards a Corruption Free Area (WBK) which are still not optimally implemented. This research aims to analyze the implementation of the Integrity Zone development program at the West Surabaya Samsat Joint Office as well as the obstacles faced in implementing the Integrity Zone development program at the West Surabaya Joint Office.The method used in this research is qualitative method. The research informant is the Head of UPT PPD West Surabaya as the Integrity Zone Supervisor who has the involvement of the Head of UPT as the leader as a role model in the Development of the Integrity Zone. The research focus uses Grindle analysis to examine the implementation of the Integrity Zone Towards a Corruption Free Area (WBK) at the West Surabaya Samsat Joint Office. Data collection techniques were carried out by interviews and observation. The research data analysis technique uses descriptive analysis. The results of the research prove that the implementation of the Integrity Zone development program at the West Surabaya Samsat Joint Office based on the Grindle policy model generally aims to reduce corrupt practices in motor vehicle services according to needs in realizing Good Governance which is supported by Human Resources, Funding and RB Ministerial Regulation No. 90 of 2021. Meanwhile, the obstacles in implementing the construction of the Integrity Zone at the West Surabaya Samsat Joint Office are Lack of Employee Awareness and Commitment, Limited Resources, Resistance and Resistance from Unsupportive Parties, Unpreparedness of Infrastructure and Technology, Patterns Old Organizational Thinking and Culture and Lack of Community Understanding and Support.